OTHER COMPREHENSIVE INCOME PADA INDUSTRI DASAR DAN KIMIA - Amhar, Nurmala; Mulyadi, JMV; Asy’ari, Asy’ari (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2017)
This study is done to present how the implementation other comprehensive income after the implementation of IFRS (Empirical Studies in Basic Industry and Chemicals listed in Indonesia Stock Exchange in 2012-2015). Data collection techniques in this study is the population data that all companies engaged in chemical and basic industry sectors listed on the Stock Exchange resulting in 64 corporate data. Data required in this study were obtained from the Indonesian Capital Market Directory (ICMD) and the Indonesia Stock Exchange (BEI). Data analysis method used is the Cross Tabulation (Crosstab) and Cramer V with the help of the SPSS statistical data processing program. The study concluded that among the companies presenting and not presenting OCI component in the Income Statement Other Kompehensif, terdepat no significant difference. This may be explained in Prob Significance of 0.10% less than 0.05% Keywords: other comprehensive income, IFRS